2016
DOI: 10.1016/j.bbacli.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response to glatiramer acetate therapy in multiple sclerosis patients

Abstract: Glatiramer acetate (GA; Copaxone) is a random copolymer of glutamic acid, lysine, alanine, and tyrosine used for the treatment of patients with multiple sclerosis (MS). Its mechanism of action has not been already fully elucidated, but it seems that GA has an immune-modulatory effect and neuro-protective properties. Lymphocyte mitochondrial dysfunction underlines the onset of several autoimmune disorders. In MS first diagnosis patients, CD4+, the main T cell subset involved in the pathogenesis of MS, undergo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“… 50 , 51 Our data, together with those from other studies, contribute to this concept by providing evidence that immunomodulatory drugs approved for the treatment of multiple sclerosis at least partly exert their effects via the modulation of metabolic pathways. 18 , 22 , 52 …”
Section: Discussionmentioning
confidence: 99%
“… 50 , 51 Our data, together with those from other studies, contribute to this concept by providing evidence that immunomodulatory drugs approved for the treatment of multiple sclerosis at least partly exert their effects via the modulation of metabolic pathways. 18 , 22 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…Given that blocking MCT-4 functions on macrophages alleviated their activation and modulated the severity of EAE disease, interfering with the glycolytic functions is an attractive therapy to treat inflammatory conditions such as MS. A recent study by Kornberg et al (64) showed that the MS drug dimethyl fumarate and its metabolite monomethyl fumarate act by inactivating the glycolytic enzyme glyceraldehyde 3-phosphate dehydrogenase in peritoneal macrophages and CD4 + T cells in both mice and humans. Similarly, glatiramer acetate (Copaxone) modulates immune infiltration in part by decreasing glycolysis within the T cells of patients with relapsing-remitting MS (RRMS) (65). Thus, targeting glycolysis in immune subsets may represent a viable therapy to treat MS.…”
Section: Discussionmentioning
confidence: 99%
“…The up‐regulation of aerobic glycolysis is mainly due to an increase of hexokinase and phosphofructokinase. Importantly, part inhibition of aerobic glycolysis by copaxone can restore mitochondrial function and reduce CD4+ T Cell dysfunctions (De Riccardis et al, ). Thus, inhibition of aerobic glycolysis may alleviate the process of MS by reducing CD4+ T Cell dysfunctions.…”
Section: The Role Of Warburg Effect In Brain Diseasesmentioning
confidence: 99%